Sunda Wiwitan: The Belief System of Baduy Indigenous Community, Banten, Indonesia - Enjang AS; Mukhlis Aliyudin; Farid Soleh Nurdin; Muhibudin Wijaya Laksana; Sitta Resmiyanti Muslimah; Widodo Dwi Ismail Azis (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2020)
The purpose of this study is to determine the construction of the meaning of Sunda Wiwitan religion in Sundanese Baduy indigenous people. The research uses interpretive paradigms with qualitative methods, and symbolic interaction study approaches as a tool of analysis. Data gathered through participatory observation and in-depth interviews. Sunda Wiwitan religion is the main symbol in the Baduy indigenous people, and is a dimension that reaches every side of life, and is a collective representation of the belief system of the Baduy indigenous community. This symbol serves as a reference for the collective paradigm, and as a reference for interpreting natural phenomena and determining the behavior of the Baduy indigenous people. The symbol of traditional institutions and traditional ceremonies represent three essential issues, namely: (1) Understanding and appreciation of religion (belief) of the Baduy indigenous people as Sunda Wiwitan descendants; (2) Observance and practice of the daily life of the Baduy indigenous people as members of the traditional Sundanese or Sunda Buhun social groups; and (3) Symbolization of the existence and recognition of the existence of government and power outside the Baduy Customary institution.